STRATEGI KOMUNIKASI PEMASARAN KAFE KOPMIL PING 2 U PEKANBARU DALAM MEMPERTAHANKAN LOYALITAS KONSUMEN - Khomsa, Fajrin Al; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
CafÃ© Kopmil Ping 2 U is one of the cafes in Pekanbaru which was established in 2012 with their menu mainstay Coffee Milo. This cafe consumers continues to increase every year. With a variety of marketing communications strategy used, this cafÃ© is managed to maintain the existence of consumers to repurchase and to establish good relations with the company. The purpose of this study is to determine how the marketing communication strategy of cafe Kopmil Ping 2 U in maintaining customer loyalty. This study uses descriptive qualitative research method to describe the state of the subject or object of the research. This study uses a model of interactive data analysis Miles and Hubermen , using a technique that checks the validity of the data through the extension of participation and triangulation. The subject of this research is the owner of cafe Kopmil Ping 2 U, the employees, Ambassador of Kopmil 2014 and fixed consumers. The subjects were selected using purposive sampling technique where the researcher determines their own subjects which were selected because of certain considerations. The results showed that the cafe Kopmil Ping 2 U has done a marketing communications strategy to retain customer loyalty. Steps taken are to establish the audience with mass promotion and market segmentation, establish communication objectives by building awareness, build knowledge, make consumers like the product, making consumers believe them, until finally they decide to buy, designing order by determining the content of the order, structure of the order , order format and determine the source of the order. This cafe also determines the communication channel to order by using interpersonal and impersonal channels, as well as determine aspects of consumer.Key word: marketing communication strategy, customer loyalty